The Dominant Factors That Influence Preferences For Visiting Grin Cafe - Sapto Usodo; Fahrul Riza; Cosmas Gatot Haryono (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to identify and map the dominant factors influencing customer visit preferences to Grin Kafe, a local café business that has two branches with different characteristics. A quantitative approach is used in this study by applying the Analytical Hierarchy Process (AHP) method, which allows analysis of the relative importance of various factors determining customer visit decisions. The two main variables analyzed include: atmosphere and interior design. Data was collected through a paired comparison questionnaire given to customers who had visited Grin Kafe. The results of the study are expected to provide an overview of the priority of customer perception of these factors, as well as become a strategic basis for the development of services and increase the attractiveness of Grin Kafe, as well as contribute to the development of consumer behavior studies in the local café sector.